Rare earth long-afterglow light-controlled luminescent material and preparation method thereof
By adjusting the composition and preparation process of rare-earth long-afterglow light-controlled luminescent materials, SrTiO3:Eu3+/SrAl2O4:Eu2+ materials were prepared, solving the problem that existing technologies can only emit a single color. This achieved a long-afterglow effect with multiple light colors, improved luminescence intensity and luminescence time, and expanded application scenarios.
Patent Information
- Application Number
- CN202411813133.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Existing rare-earth long-afterglow luminescent materials can only emit light of one color, which limits their application in scenarios requiring multiple color changes.
By adjusting the composition and preparation process of rare-earth long-afterglow light-controlled luminescent materials, especially by controlling the molar ratio of Ti:Sr:Al:Eu:Dy and using reducing agent carbon powder, SrTiO3:Eu3+/SrAl2O4:Eu2+ materials were prepared, enabling them to emit multiple colors of light under dark conditions and store and release light energy under illumination.
It achieves a long afterglow effect by emitting multiple different colors of light in the dark, with excellent luminous intensity and long luminous time, making it suitable for anti-counterfeiting, clothing and lighting fields, thus broadening its application scope.
Smart Images

Figure CN119286521A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a rare earth long afterglow light-controlled luminescent material and a preparation method thereof, belonging to the technical field of luminescent materials containing rare earth metals. Background Art
[0002] In recent years, luminescent materials have been widely used in daily clothing, plush toys, stage performances, traffic safety and other fields, and various clothing products made of luminescent materials have also attracted much attention. 3+ / SrAl2O4:Eu 2+ As a type of rare earth long afterglow luminescent material, the composite luminescent material has shown great potential in anti-counterfeiting, clothing and lighting. It can absorb and store energy under visible light and emit visible light of various colors in the dark, with warning, lighting or anti-counterfeiting functions.
[0003] At present, the preparation and application of rare earth long afterglow luminescent materials are very extensive. For example, CN1221631C discloses a method for preparing a rare earth green long afterglow luminescent material, which is prepared by mixing and sintering CaCO3, MgO, SiO2, CaCl2 and a solvent B2O3 to produce a rare earth luminescent material that can emit green long afterglow light, with good afterglow brightness and slow afterglow decay. CN102493017A discloses a method for preparing a rare earth silicate blue long afterglow polyester fiber, which is prepared by mixing, drying and a special spinning process for polyester spinning, rare earth magnesium strontium silicate and nano-functional additives to produce a fiber material that can emit blue long afterglow, with excellent blue light long afterglow performance. CN101139743A discloses a special rare earth luminescent fiber for anti-counterfeiting, which uses a rare earth luminescent material as a matrix, polyester, polypropylene or polyamide as a carrier, and is prepared in combination with a special spinning process. The produced rare earth luminescent fiber has a different emission spectrum, similar to a fingerprint, and is unique, and can be applied to anti-counterfeiting technology.
[0004] The rare earth long afterglow luminescent materials prepared and applied by the above scheme have excellent luminous intensity and long-lasting luminous attenuation performance, but can only emit light of one color, which limits its application in luminescence, lighting, clothing color and other scenes that require a variety of complex color changes. Summary of the invention
[0005] In view of this, the present application first provides a rare earth long afterglow light-controlled luminescent material, which has a "red shift" effect, moving the original multiple different light colors to the red band, and then emitting a variety of different light colors that are more reddish, solving the problem of the lack of long afterglow luminescent materials that emit multiple different light colors in the prior art.
[0006] Specifically, the present application is implemented through the following scheme: A rare earth long afterglow light-controlled luminescent material, the rare earth long afterglow light-controlled luminescent material is recorded as SrTiO3:Eu 3+ / SrAl2O4:Eu 2+ , and the molar ratio satisfies Ti: Sr: Al: Eu: Dy = x: 1: 2: y: 0.03, x = 0.1 ~ 1, y = 0.02 ~ 0.08, and it can emit a variety of light colors in the dark, with an afterglow time of ≥ 1000 seconds and an afterglow intensity of ≥ 0.217 cd / m 2 .
[0007] The above-mentioned rare earth long afterglow light-controlled luminescent material can absorb light energy under visible light or ultraviolet light for a short period of time. After the light source disappears, it gradually releases the stored light energy in the form of visible light of different colors, and the luminescence phenomenon can continue for a certain period of time.
[0008] Further, as a preference: The rare earth long afterglow luminescent material absorbs visible light or ultraviolet light and emits a variety of light colors, including blue-purple, orange, light orange, pink, green, bright green, gray, and tender pink.
[0009] The second purpose of the applicant is to provide a method for preparing a rare earth long afterglow light-controlled luminescent material, characterized in that: TiO2, SrCO3, Al2O3, Eu2O3, and Dy2O3 are used as raw materials, the raw materials are fully ground after adding the auxiliary solvent H3BO3, and then the reducing agent carbon powder is added, and the raw materials are placed in a high-temperature calcining furnace for calcination, and then naturally cooled and annealed, and then ground into powder again, that is, the rare earth long afterglow light-controlled luminescent material SrTiO3:Eu 3+ / SrAl2O4:Eu 2+ , the molar ratio of TiO2, SrCO3, Al2O3, Eu2O3 and Dy2O3 is 0.1~1:1:1:0.01~0.04:0.015.
[0010] The molar ratio of each material of the above raw materials is sufficient to give the material the performance of different luminous colors and luminous intensities under dark conditions.
[0011] The calcination reaction temperature is 1100-1500°C, and the calcination time is 3-8 hours. More preferably, the calcination temperature is increased from room temperature to the reaction temperature at a heating rate of 5°C / min.
[0012] The molar ratio of the carbon powder to Eu2O3 is 0-2:1, preferably 1-2:1, that is, it is best to ensure sufficient excess.
[0013] Through the above preparation method, the rare earth long afterglow luminescent material produces a "red shift", moving from the original non-luminescent, blue light, and green light to the red band, emitting a more reddish light color, and thus producing light of different colors.
[0014] The above-mentioned rare earth long afterglow light-controlled luminescent material has excellent luminous brightness and luminous time, and can emit light of various colors in a dark state, and make the main wavelength of the existing rare earth long afterglow luminescent material move toward the red band, producing a "red shift", and emitting a more reddish light color in a dark state. Therefore, it can be used in anti-counterfeiting, clothing, lighting and other fields.
[0015] The light-controlled luminescent material in this case needs to be placed under light or visible light for a period of time before use to absorb and store energy. After the light source is withdrawn, the energy is released in the form of visible light, which appears as visible blue-green, orange-yellow, purple, red and other visible light.
[0016] The present application can realize the shift of the main wavelength of the luminescent material to the red band, producing a "red shift", and endowing the existing rare earth long afterglow luminescent material with a luminescent state in the dark state from the original non-luminescent, blue light, and green light to the red band, thereby emitting a more reddish light color, such as blue-purple light changing to orange light, pink light changing to red light, thereby producing a variety of different light colors.
[0017] The beneficial effects of the present invention are: (1) Excellent luminous intensity: The present invention controls the use of reducing agents such as carbon powder to make part of Eu 3+ Reduced to Eu 2+ , and then synthesize SrAl2O4:Eu 2+ and SrTiO3:Eu 3+ , so that the material can produce obvious red light luminescence phenomenon at night. The composite luminescent material SrTiO3:Eu 3+ / SrAl2O4:Eu 2+ The luminous intensity is excellent, which significantly improves the lighting effect of the product in the dark and broadens its application range in night lighting, luminous clothing and other fields.
[0018] (2) Obvious "red shift" effect: The present invention controls the use of TiO2 concentration and changes the ratio of Ti:Sr in the raw material, so that the main wavelength of the product moves to the red band, resulting in a "red shift" phenomenon. Specifically, the matrix SrAl2O4:Eu 2+ ,Dy 3+ The emitted visible light is green light. After the preparation process of the present invention, the product can produce red visible light; the material that originally emits blue-violet light can also be shifted to the red light band to emit orange light; the material that originally emits pink light can be shifted to the red light band to emit red light. The obvious "red shift" effect can help the material shift to red light during preparation, meeting the preparation needs of rare earth long afterglow light-controlled luminescent materials.
[0019] (3) Long-lasting luminescence time: In the present invention, when the luminescent material receives light, Eu 2+ The outer electrons of the ion generate 4f 6 5d 1 →4f 7 The material absorbs light energy through relaxation and stores it in the material's unique defect energy level. When the material leaves the light source, the electrons captured by the defect energy level will be slowly released, giving the material a long afterglow characteristic. TiO2, as a photocatalyst, greatly improves the material's absorption and conversion of light energy. The material can absorb the energy of visible light and ultraviolet light, and emit bright visible light of various colors in the dark, which can last for more than 1,000 seconds.
[0020] (4) Excellent emission light and excitation light absorption effect: The present invention controls the use of reducing agent carbon powder and TiO2 concentration to produce sufficient Eu in the material. 2+ When receiving visible light or ultraviolet light, the material undergoes energy level transition, and TiO2 acts as a photocatalyst, which greatly enhances the material's absorption of light, thereby enhancing the material's absorption of emitted light and excitation light.
[0021] This application has successfully solved the problems of lack of long afterglow luminescent materials with different light colors, short luminescence time and low luminescence intensity in previous products by optimizing the preparation process of rare earth long afterglow materials. It can produce a "red shift" effect with existing rare earth long afterglow luminescent materials with different light colors, and then form any light color. At the same time, the product has excellent luminescence intensity, obvious "red shift" effect, long-lasting luminescence time, excellent emission light, excitation light absorption effect and other properties, and is suitable for lighting, anti-counterfeiting and clothing and other fields, with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 The SEM photos of the luminescent materials prepared in Examples 1 to 4 are as follows: (a) is a SEM photo of Example 1, (b) is a SEM photo of Example 2, (c) is a SEM photo of Example 3, and (d) is a SEM photo of Example 4; Figure 2 This is the EDS Mapping image of the luminescent material prepared in Example 5; Figure 3 This is an EDS Mapping photo of the luminescent material prepared in Example 6; Figure 4 This is an EDS Mapping photo of the luminescent material prepared in Example 7; Figure 5 This is an EDS Mapping photo of the luminescent material prepared in Example 8; Figure 6 XRD diagram of the luminescent material prepared in each embodiment; Figure 7 The emission spectra of the luminescent materials prepared in each embodiment; Figure 8 The excitation spectrum of the luminescent material prepared in each embodiment; Fig. 9 The afterglow attenuation curve of the luminescent material prepared in each embodiment; Fig.10 The initial brightness and steady-state brightness diagram of the dilute luminescent material prepared in each embodiment; Fig.11 Chromaticity diagram of light emitted by the luminescent material prepared in each embodiment; Fig.12 These are comparison diagrams of the luminescent materials prepared in various embodiments before and after absorbing light. DETAILED DESCRIPTION
[0024] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0025] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments. The raw materials used in the present invention are all commercially available unless otherwise specified.
[0026] The microscopic morphology of the material was tested by a scanning electron microscope (Su1510) to obtain the SEM photos of the material; the phase composition of the sample was tested by a light tube X-ray diffractometer (ARL XTRA); the emission spectrum and excitation spectrum of the material were tested by an FS5 fluorescence spectrometer (SC-10) to obtain the emission spectrum and excitation spectrum under different conditions; the afterglow brightness and afterglow time of the material were tested by a fluorescence afterglow brightness tester (PR-305) to obtain the afterglow curve, initial brightness and steady-state brightness diagram.
[0027] Example 1
[0028] The preparation process of the rare earth long afterglow light-controlled luminescent material in this embodiment is as follows: Step 1, according to the molar ratio of Ti: Sr: Al: Eu: Dy: carbon powder = 1: 1: 2: 0.05: 0.03: 0.025, take SrCO3, Al2O3, TiO2, Eu2O3, Dy2O3 and carbon powder (that is, the molar ratio of TiO2, SrCO3, Al2O3, Eu2O3, Dy2O3 and carbon powder is 1: 1: 1: 0.025: 0.015: 0.025), then weigh the solvent H3BO3, mix the raw materials SrCO3, Al2O3, TiO2, Eu2O3, Dy2O3 and the solvent H3BO3, put them into a mortar, and grind them thoroughly for 1 hour, wherein H3BO3 accounts for 3% of the total molar amount of the raw materials.
[0029] Step 2: Put the ground powder into a crucible, place it in a high-temperature calcining furnace, add the carbon powder taken according to the above proportion, and raise the temperature in the high-temperature calcining furnace from room temperature to 1200° C. at a heating rate of 5° C. / min. After calcining at 1200° C. for 4 hours, annealing is performed for 4 hours; Step three, after the annealed material is naturally cooled, the crucible is taken out and the material is fully ground again for 1 hour to obtain a rare earth long afterglow light-controlled luminescent material.
[0030] Example 2
[0031] The configuration of this embodiment is the same as that of Embodiment 1, except that in step 1, Ti:Sr:Al:Eu:Dy:carbon powder=1:1:2:0.08:0.03:0.025.
[0032] Example 3
[0033] The configuration of this embodiment is the same as that of Embodiment 1, except that in step 1, Ti:Sr:Al:Eu:Dy:carbon powder=1:1:2:0.02:0.03:0.025.
[0034] Example 4
[0035] The configuration of this embodiment is the same as that of Embodiment 1, except that in step 1, Ti:Sr:Al:Eu:Dy:carbon powder=1:1:2:0.03:0.03:0.025.
[0036] Example 5
[0037] The configuration of this embodiment is the same as that of Embodiment 1, except that in step 1, Ti:Sr:Al:Eu:Dy:carbon powder=0.1:1:2:0.05:0.03:0.025.
[0038] Example 6
[0039] The configuration of this embodiment is the same as that of Embodiment 1, except that in step 1, Ti:Sr:Al:Eu:Dy:carbon powder=0.1:1:2:0.08:0.03:0.025.
[0040] Example 7
[0041] The configuration of this embodiment is the same as that of Embodiment 1, except that in step 1, Ti:Sr:Al:Eu:Dy:carbon powder=0.1:1:2:0.05:0.03:0.0125.
[0042] Example 8
[0043] The configuration of this embodiment is the same as that of Embodiment 1, except that in step 1, Ti:Sr:Al:Eu:Dy:carbon powder=0.1:1:2:0.08:0.03:0.0125.
[0044] The performance test results of the products obtained in the above embodiments are as follows: Figure 1 to Figure 12 shown.
[0045] Figure 1 The SEM photos of the rare earth long afterglow light-controlled luminescent materials prepared in Examples 1 to 4, a corresponds to Example 1: the surface of the material is uneven, the particle distribution is relatively dispersed and uneven, there is agglomeration, and small particles are dispersed around the large particles, where the diameter of the small particles is about 10μm, and the diameter of the large particles is about 50μm. This phenomenon is also consistent in b corresponding to Example 2, c corresponding to Example 3, and d corresponding to Example 4.
[0046] Figure 2~Figure 5 The EDS Mapping images of the luminescent materials prepared in Example 5 to Example 8 are as follows: the materials are mainly composed of Sr, Eu, O, Al and Ti elements, and the Si element in the EDS results comes from the silicon wafer substrate.
[0047] Figure 6The XRD spectrum of the rare earth long afterglow light-controlled luminescent material prepared in Example 1 to Example 4 shows the main components of the material. Through XRD spectrum analysis, it can be seen that the main components of the material are SrTiO3:Eu 3+ / SrAl2O4:Eu 2+ .
[0048] Figure 7 The emission spectrum of the luminescent material prepared in the above examples shows the emission intensity of the material under different wavelengths of emission light (400-680nm). By comparison, it can be observed that the emission spectrum of the prepared luminescent material is a broadband spectrum from 420nm to 680nm, and there are 3 emission peaks in Examples 1 to 4, which are 592nm, 618nm and 640nm respectively; there are 3 emission peaks in Examples 5 and 6, which are 518nm, 618nm and 640nm respectively; and the performance of Example 7 is consistent with that of Example 8, with 1 emission peak at 640nm.
[0049] Figure 8 The excitation spectra of the luminescent materials prepared in the above examples show the excitation intensity of the materials under different wavelengths of excitation light (300-500nm). By comparison, it can be observed that the excitation spectra of the rare earth red long afterglow luminescent materials in Examples 1-4 and Examples 7 and 8 are narrower, with only one excitation peak at 415nm. The excitation spectra of Examples 5 and 6 are wider, between 350nm and 450nm, with two excitation peaks at 374nm and 415nm, respectively. This shows that the excitation intensity of the material is strong and its absorption effect on the excitation light is good.
[0050] Fig. 9 The afterglow decay curve of the luminescent materials prepared in the above-mentioned embodiments shows that the afterglow decay of the materials prepared in each case experienced two processes: fast decay and slow decay. The initial brightness of Embodiments 1 to 4 and 5 when the illumination was stopped was relatively high. Within the following 100 seconds, the afterglow brightness decayed rapidly; at about 500 seconds, the brightness decay reached a stable state. The afterglow luminescence time of the material can reach 1000 seconds, and the luminescence time of the material is long. The initial brightness of Embodiment 1 is only 2.7% of that of Embodiment 5, and the initial brightness of Embodiment 2 is only 7.8% of that of Embodiment 6. Even in the case of insufficient carbon, the initial brightness of Embodiments 7 and 8 is higher than that of Embodiments 3 and 4. The initial brightness of Embodiment 3 is only 69.2% of that of Embodiment 7, and the initial brightness of Embodiment 4 is only 78.3% of that of Embodiment 8, but both can achieve an afterglow luminescence time of 1000 seconds. The luminescence is mainly Eu 3+ and Eu 2+The above embodiments also indirectly confirm that, in this aspect, TiO2 has a more significant impact on the ability of the prepared luminescent material to absorb light energy.
[0051] Fig.10 The initial brightness and steady-state brightness of the luminescent materials prepared in the above examples are shown in Figure 1. The initial brightness of Example 5 is the highest, which is 0.217 cd / m 2 , which is significantly higher than the other cases; the steady-state brightness of Example 5 is also higher than the other examples. This shows that the material has high luminous brightness and excellent luminous performance.
[0052] In comparison, Examples 1 to 4 have poor absorption of emitted light and excitation light, low afterglow brightness, and short luminous time, which greatly affects the luminous effect at night.
[0053] Fig.11 The chromaticity diagram of the emitted light of the luminescent materials prepared in the above embodiments shows that the material in embodiment 1 can emit more red visible light. By comparing all the cases with the matrix SrAl2O4:Eu 2+ ,Dy 3+ It can be seen from the chromaticity region that the main wavelength of all cases moves to the red light wavelength band. Among them, the emission light of Example 1 is located in the blue-purple light region, and the emission light of Example 2 is located in the orange light region. The afterglow brightness of Example 3 is slightly lower than that of Example 1, and its emission light is located in the light orange light region. The afterglow brightness of Example 4 is slightly lower than that of Example 1, but higher than that of Example 3, and its emission light is located in the pink light region. Compared with the matrix SrAl2O4:Eu 2+ ,Dy 3+ In the chromaticity region, the "red shift" phenomenon occurred in Examples 2, 3, and 4. The emission light of Examples 5 and 6 is both located in the green light region, emitting green light; the emission light of Example 7 is located in the gray light region, emitting gray light; the emission light of Example 8 is located in the tender pink light region, emitting tender pink light, and there is a "red shift" phenomenon.
[0054] Fig.12 This is a comparison diagram of the luminescent materials prepared in the above examples before and after absorbing light. After being irradiated with visible light or ultraviolet light, each luminescent material emits visible light of various different colors, indicating that the material can produce long afterglow visible light of various colors, with many types of luminescence.
[0055] It can be seen from the above embodiments that the luminescent material in the present application exhibits excellent performance in many aspects, especially in the absorption effect of emitted light and excitation light, afterglow brightness and luminescence time, and "red shift" which are superior to other methods.
[0056] In addition, the applicant also conducted tests on the effect of the amount of reducing agent carbon powder added, and the results are shown in Table 1.
[0057] Example 9
[0058] The configuration of this embodiment is the same as that of embodiment 1, except that the amount of carbon powder added is as shown in Table 1.
[0059] Table 1: Effect of different carbon powder addition amounts (molar ratio relative to Eu) on product performance Toner Addition Amount Peak change Afterglow initial brightness and luminous duration Color light 0 There are three emission peaks at 592nm, 618nm, and 640nm; and one excitation peak at 415nm. <![CDATA[The initial luminance of the afterglow is 0.01069 cd / m 2 , and the afterglow emission time ≥ 1000 seconds.]]> Compared with Example 1, a "red shift" is produced, and the emission light region is located in the light red light region. 0.0125 There are two emission peaks at 592nm and 618nm; and one excitation peak at 415nm. <![CDATA[The initial brightness of the afterglow is 0.0072 cd / m 2 , and the afterglow emission time ≥ 1000 seconds.]]> Compared with Example 1, a "red shift" occurs, and the emission light region is a red light region. Comparison of Example 1 and Example 9 shows that the introduction of carbon powder makes part of Eu 3+ Reduced to Eu 2+ , and then synthesize SrAl2O4:Eu 2+ and SrTiO3:Eu 3+ , so that the material can produce obvious red light luminescence phenomenon at night. When added in insufficient amount in Example 9, the light emitted by the prepared luminescent material is different from that in Example 1.
[0060] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.
Claims
1. A rare earth long afterglow light-controlled luminescent material, characterized in that: The rare earth long afterglow light-controlled luminescent material is recorded as SrTiO3:Eu 3+ / SrAl2O4:Eu 2+ , and the molar ratio satisfies Ti: Sr: Al: Eu: Dy = x: 1: 2: y: 0.03, x = 0.1 ~ 1, y = 0.02 ~ 0.08, and it can emit a variety of light colors in the dark, with an afterglow time of ≥ 1000 seconds and an afterglow intensity of ≥ 0.217 cd / m 2 .
2. The rare earth long afterglow light-controlled luminescent material according to claim 1, characterized in that: The multiple light colors include blue-purple, orange, light orange, pink, green, bright green, gray, and tender pink.
3. A method for preparing a rare earth long afterglow light-controlled luminescent material, characterized in that: TiO2, SrCO3, Al2O3, Eu2O3, and Dy2O3 are used as raw materials. After adding H3BO3 and grinding them fully, carbon powder is added, calcined in a high-temperature calcining furnace, naturally cooled and annealed, and ground into powder again, which is the rare earth long afterglow light-controlled luminescent material SrTiO3:Eu 3+ / SrAl2O4:Eu 2+ , the molar ratio of TiO2, SrCO3, Al2O3, Eu2O3 and Dy2O3 is 0.1~1:1:1:0.01~0.04:0.
015.
4. The method for preparing a rare earth long afterglow light-controlled luminescent material according to claim 3, characterized in that: The molar ratio of the carbon powder to Eu2O3 is 0~2:
1.
5. The method for preparing a rare earth long afterglow light-controlled luminescent material according to claim 3 or 4, characterized in that: The molar ratio of the carbon powder to Eu2O3 is 1-2:
1.
6. The method for preparing a rare earth long afterglow light-controlled luminescent material according to claim 3, characterized in that: The reaction temperature of the calcination is 1100-1500° C., and the calcination time is 3-8 hours.
7. The method for preparing a rare earth long afterglow light-controlled luminescent material according to claim 3, characterized in that: The molar ratio of TiO2, SrCO3, Al2O3, Eu2O3, Dy2O3 and carbon powder is 0.1:1:1:0.025~0.04:0.015:0.025, and the added amount of H3BO3 is 3% of the total molar amount of raw materials.
8. The method for preparing a rare earth long afterglow light-controlled luminescent material according to claim 3, characterized in that: The cooling annealing time is 4 to 6 hours.
9. An application of a rare earth long afterglow light-controlled luminescent material, characterized in that: The rare earth long afterglow light-controlled luminescent material is used for anti-counterfeiting materials, warning clothing or lighting materials.
Citation Information
Patent Citations
Fluorescent material for LED and preparation method thereof
CN101838533A
Alkali-metal-ion-reinforced red light type fluorescent powder formed by adulterating titanate in rare earth and preparation method
CN105199725A
Near-infrared light charging upconversion-long-afterglow orthogonal fluorescence-coded anti-counterfeit material
CN106978181A
Microwave synthesis of a white rare earth long-afterglow luminescent material suitable for ultraviolet excitation
CN107353894A
Particle surface coating method, and article and electroluminescent element produced thereby
CN1493646A